Extraction of sodium alginate by dielectric barrier discharge (DBD) plasma and the comparative study on rheological features - Xinting Zhang; Chaohui Wang; Ke Liu; Yuying Zhang; Jingfeng Yang (Food Hydrocolloids, 2026)

The toxicity of petroleum pollutants on marine zooplankton: Multiscale effects from individuals to populations - Tianrui Liu; Xiahui Liu; Wangguangming Yu; Jingfeng Bai; Wei Shen; Xuan Wu (Marine Pollution Bulletin, 2026)

Geomorphic conditions and anthropogenic irrigation as drivers of CO2 and CH4 emissions in Heihe River - Zhiheng Du; Wenhan Hu; Hao Cui; Lei Wang; Jingfeng Liu; Fangping Yan; Rinat Manasypov; Changlian Tao; Renjun Wang; Jing Luo; Chuntan Han; Xiqiang Wang (Global and Planetary Change, 2026)

The fluidization dynamics of binary particles in a supergravity swirling liquid-solid fluidized bed using coupled MPPIC-VOF approach - Hailong Tang; Jingfeng He; Liangyu Yao; Dongyao Wang; Lixiang Fu; Bin Yang; Lingtao Zhu; Yuhao Liu (Chemical Engineering Journal, 2026)

Responses of evapotranspiration and gross primary productivity to extreme vapor pressure deficit, shortwave radiation, and soil moisture across China - Yi Liu; Jingfeng Xiao; Xing Li; Yue Li (Agricultural and Forest Meteorology, 2026)

Developmental toxicity assessment of Allura Red AC in SD rats: A focus on skeletal ossification - Penghe Liu; Fang Tan; Jingfeng Sun; Yanwu Wang; Liying Zhou; Danlian Liang; Guangqiu Qin (Reproductive Toxicology, 2026)

The rectal sac as a second liver for detoxification in the metamorphosing silkworm - Rongbing Chen; Jingfeng Yang; Shoulin Zhu; Erjun Ling; Qiuning Liu; Wuren Huang (Journal of Insect Physiology, 2026)

Can digital transportation contribute to mitigating environmental pollution? Evidence from the Chinese Context - Rui Liu; Liyin Shen; Jingfeng Yuan (Journal of Cleaner Production, 2026)

Metal-free activation of peroxymonosulfate by natural organic acid or inorganic acid for wastewater disinfection and emerging contaminants degradation - Ying Liu; Jingfeng Gao; Yameng Wang; Yan Guo; Yi Zhang (Chemical Engineering Journal, 2026)

Strengthening carbon sinks in Tibetan Plateau alpine grasslands over the past four decades - Yuyang Wang; Yaoming Ma; Jingfeng Xiao; Weiqiang Ma; Zhipeng Xie; Zhiyong Ding; Kesi Liu (Agricultural and Forest Meteorology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

UAV coarse visual localization in large-scale continuous scenes - Cheng Bi; Jingfeng Wang; Zhengxi Li; Yang Zhao; Zhiyu Jiang; Yuan Yuan; Ganchao Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Cynaroside reduces neutrophil extracellular trap formation and disease severity in a mouse model of asthma by inhibiting the COX-2/TNF-alpha/NF-kB axis - Daowen Yang; Jingfeng Liu; Qiao Wang; Jiawen Li; Chuanxi Tian; Ziqing Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Asynchronous alterations in bacterial composition and function increased functional redundancy related to greenhouse gas emissions following coastal habitat transitions - Jichen Qiu; Junhong Bai; Di Wang; Yuhao Xu; Yue Liu; Yujia Zhai; Jingfeng Wang; Changhong Xiao; Langying Long; Huihua Lyu; Mengwei Chu (Marine Pollution Bulletin, 2026)

Transformation mechanisms of dissolved organic matter in a full-scale initial rainwater treatment plant: An empirical study based on ultra-high-resolution mass spectrometry and microbial community analysis - Xiaowen Chen; Qiankun Liu; Shengjie Zhao; Jingwei Feng; Jingfeng Wang; Hao Yin; Daoyun Wu (Journal of Environmental Chemical Engineering, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Rapid and efficient inactivation of Pseudocohnilembus persalinus in aquaculture water using O3/H2O2 advanced oxidation technology - Yuwei Cui; Jingfeng Jia; Xiaojuan Shao; Wulong Jiang; Wenke Liu; Hua Wang; Ruijun Li; Zhongming Huo (Aquaculture International, 2026)

Habitat changes induced by converting coastal aquaculture to wetlands enhance taxonomic diversity and cross-species interaction strength of macro- and meiobenthos - Jichen Qiu; Wenjing Cao; Zhaohan Zhang; Junhong Bai; Liangxing Cao; Yuhao Xu; Jiajie Mei; Yaqi Wang; Yue Liu; Jingfeng Wang; Yanan Zhang (Aquaculture, 2026)

Optimization of friction medium rod shape and its enhanced pre-concentration of coal-hosted graphite ore by triboelectric separation - Yuhao Liu; Jingfeng He; Wenjie Tang; Shuaixing Shi; Lingtao Zhu; Bin Yang (Minerals Engineering, 2026)

Metabolic exploration of glycogen accumulating organisms’ sludge with Candidatus Contendobacter in enhanced biological phosphorus removal - Shang Wang; Yuchao Liu; Yujie Cai; Xuan Wang; Bin Xue; Sheng Li; Yiqiu Fang; Chao Li; Jingfeng Wang (Journal of Environmental Sciences, 2026)

Experimental study on punching shear performance of embedded special-shaped CFST column base - Yong Liu; Zhuofei Li; Jingfeng Wang; Lanhui Guo; Fan Ye; Shasha Tan; Beibei Li (Engineering Structures, 2026)

Editor's note to “The Grain-for-Green project offsets warming-induced soil organic carbon loss and increases soil carbon stock in Chinese Loess Plateau” [Sci. Total Environ. 837 (2022), 155469] - Huiwen Li; Yiping Wu; Shuguang Liu; Wenzhi Zhao; Jingfeng Xiao; Leigh A. Winowiecki; Xiaowei Yin; Fan Wang; Bellie Sivakumar; Yue Cao; Pengcheng Sun (Science of The Total Environment, 2026)

Stronger Sensitivity of Plant Photosynthesis to Rising CO 2 in High Elevation Ecosystems - Yao Chen; Yangjian Zhang; Zhihua Liu; Shilong Piao; Jingfeng Xiao; Ashley Ballantyne; Philippe Ciais; Josep Peñuelas; Jie Gao; Yongwen Liu; Lin Jiang; Juntao Zhu; et al. (Ecology Letters, 2026)
The CO 2 ‐fertilisation effect (CFE) on vegetation productivity is the major driver of the enhanced land carbon sink in recent decades. CFE theoretically increases with elevation due to the higher sensitivity of carboxylation to an increase of CO 2 under lower CO 2 partial pressure, but the elevation‐dependent CFE pattern has been largely overlooked. By conducting a 6‐year CO 2 enrichment experiment (+100 ppm) in an alpine grassland, we show that elevated CO 2 increased gross primary production (GPP) by 25.5% ± 4.6%. Water availability and plant biomass allocation modulates CFE during different seasons. A global synthesis of 10 CO 2 enrichment experiments reveals that CFE increased with elevation. The satellite‐based EC‐LUE model also demonstrates a positive global elevation‐dependent CFE pattern, albeit substantially weaker than that from experimental observations. Current terrestrial biosphere models, however, could not represent the elevation‐dependent pattern, highlighting the need to improve the representations of plants' elevational physiological adaptation to rising CO 2 in models.

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Multidrug-resistant plasmid modulates ammonia oxidation efficiency in Nitrosomonas europaea through cyclic di-guanylate and acyl-homoserine lactones pathways - Jinrui Cao; Chen Zhao; Lin Bo; Xinxin He; Yuchao Liu; Shang Wang; Bin Xue; Jingfeng Wang (Bioresource Technology, 2026)

Temporal Memory Mechanisms and Biome‐Specific Drivers of Ecosystem Carbon Flux: Insights From Explainable Deep Learning Modeling - Teng Ma; Wei He; Shuangxi Fang; Jingfeng Xiao; Ngoc Tu Nguyen; Hua Yang; Peipei Xu; Chengcheng Huang; Mengyao Zhao; Shuai Liu; Xinhui Lei; Ziyi Huang (Global Change Biology, 2026)
Ecosystem carbon dynamics are governed by complex temporal dependencies and environmental interactions, yet these processes remain poorly understood and quantified across diverse biomes. Here, we developed an explainable LSTM‐Attention framework that integrates LSTM networks, attention mechanisms, and gradient‐based attribution methods to reveal temporal dependencies in ecosystem carbon flux responses by analyzing eddy covariance flux measurements from 71 sites spanning eight North American biomes. Using this approach, we identified three distinct temporal memory patterns governing carbon flux responses. Grasslands exhibit short‐term memory dominance with exponentially increasing temporal contributions from distant to recent past. Deciduous broadleaf forests and wetlands show long‐term memory dominance, with deciduous broadleaf forests displaying the strongest historical dependence (attribution values declining from 0.30 at 6 months to 0.045 at 1 month). Croplands and evergreen needleleaf forests demonstrate U‐shaped dual memory patterns. Building on these temporal patterns, we identified biome‐specific environmental drivers operating within each memory framework: wetlands primarily controlled by soil moisture, evergreen needleleaf forests by radiation, and closed shrublands by vapor pressure deficit. Beyond individual drivers, we uncovered critical nonlinear interactions that diverged from linear correlations at most sites (55 of 71 with ρ

Pre-occupation strategy towards high initial coulombic efficiency in Mn-based layer cathode for magnesium-based hybrid-ion batteries - Yipeng Liu; Baihua Qu; Junhao Zhang; Hongfei Zheng; Le Tong; Yue Hao; Dong Wang; Guangsheng Huang; Qian Li; Xiaoyuan Zhou; Dong-Liang Peng; Jingfeng Wang (Chemical Engineering Journal, 2025)

Multi-parameter input damage limit prediction for bare reinforced concrete frames using XGBoost - Chen Xiong; Yuchao Cao; Jingfeng Zheng; Linlin Xie; Liu Mei; Lixiao Li; Wujian Long (Soil Dynamics and Earthquake Engineering, 2025)

Radical-free ultra-rapid disinfection: Application of the periodate/Mn(II) system in eliminating antibiotic-resistant bacteria and genes and degrading emerging contaminants - Yameng Wang; Jingfeng Gao; Yan Guo; Lei Wei; Ying Liu; Feifei Gao; Qiyue Zuo; Ke Li (Journal of Hazardous Materials, 2025)

Mechanical analysis of eccentrically loaded SFRC columns reinforced by high-strength rebars: Testing and FE modelling - Ziming Hu; Jingfeng Wang; Qihan Shen; Beibei Li; Yong Liu (Engineering Structures, 2025)

Biases in radiative flux observations due to precipitation across the Arctic forest-tundra ecotone - Taeho Kim; Wenbo Zhou; Vinh Ngoc Tran; Liujing Zhang; Jingfeng Wang; Modi Zhu; Aleksey Y. Sheshukov; Tianqi Zhang; Desheng Liu; Valeriy S. Mazepa; Alexandr A. Sokolov; Victor V. Valdayskikh; et al. (Agricultural and Forest Meteorology, 2025)

Coupled retrieval of turbulent heat fluxes and gross primary productivity via the assimilation of land surface temperature data from geostationary satellites - Zongbin Xu; Tongren Xu; Xinlei He; Jingfeng Xiao; Sayed M. Bateni; Changhyun Jun; Gangqiang Zhang; Wenting Ming; Shaomin Liu (Remote Sensing of Environment, 2025)

A trilaminar edible film of nanocellulose, konjac glucomannan, and curcumin with pH-responsive and amphiphilic properties: preparation, characterization, and application - Xiaoyan Wang; Chaohui Wang; Jun Zhao; Xinting Zhang; Ke Liu; Jingfeng Yang (Food Chemistry, 2025)

Hypertension Induces Cognitive Impairment and Alterations of Acetylcholine Receptor mRNA Expression in the Hippocampus and Cortex of Mice - Jingfeng Liu; Jianting Hou; Jianlin Wu; Wenjun Chen (NeuroMolecular Medicine, 2025)

Estimating carbon fluxes over North America using a physics-constrained deep learning model - Bin Fan; Hankui K. Zhang; Zhongbin B. Li; Jingfeng Xiao; Xianghong Che; Zhihua Liu; Gustau Camps-Valls; Jing M. Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Responses mechanisms of resistance genes in partial nitrification and anammox system under single and combined exposure to polystyrene nanoplastics and dodecyl dimethyl benzyl ammonium chloride - Yi Zhang; Jingfeng Gao; Yi Guo; Ying Liu; Tian Xie; Hongxin Xu; Hanyi Wang (Chemical Engineering Journal, 2025)

A data-driven and knowledge graph-based research on safety risk-coupled evolution analysis and assessment in shield tunneling - Xuewei Li; Shuchen Li; Jingfeng Yuan; Zeen Wan; Xuan Liu (Tunnelling and Underground Space Technology, 2025)

Integrating the Maximum Entropy Production model and airborne imagery for understorey evapotranspiration mapping - Wenjie Liu; Okke Batelaan; David Bruce; Jingfeng Wang; Hugo Gutierrez; Hailong Wang; Robin Keegan-Treloar; Jianfeng Gou; Robert Keane; Jessica Thompson; Huade Guan (Journal of Hydrology, 2025)

Numerical analysis and calculation methods on the axial-loaded compressive behavior of cross-shaped partially encased concrete composite columns - Shuqing Tao; Yong Liu; Jingfeng Wang; Peng Gao; Qijun Yu; Qiuyu Xu; Jingzhe Li (Engineering Structures, 2025)

A strategy to improve the detection accuracy and universality of highland barley muti-quality attributes based on near infrared spectroscopy combined with model transfer method - Linglei Li; Long Li; Jingfeng Li; Jingjing Yang; Lang Jia; Bei Fan; Litao Tong; Liya Liu; Yatao Huang; Xiaolong Yang; Fengzhong Wang; Lili Wang (Food Chemistry, 2025)

Deciphering the interfacial electrochemistry of non-nucleophilic Mg(TFSI)2 as 4 V-class electrolyte for Mg batteries - Lu Zhang; Yuping Liu; Xiaolei Wang; Zhihong Cui; Chenlong Xiao; Changguo Chen; Jingfeng Wang; Guangsheng Huang; Dingfei Zhang; Fusheng Pan (Chemical Engineering Journal, 2025)

Microplastics enhance the denitrification of glycogen-accumulating organisms by regulating electronic transport in carbon-nitrogen coupling - Yuchao Liu; Jinrui Cao; Sheng Li; Xinxin He; Bin Zhang; Shang Wang; Jingfeng Wang (Journal of Hazardous Materials, 2025)

Identification of carbon dioxide and methane emission characteristic across Heihe River, China - Wenhan Hu; Zhiheng Du; Lei Wang; Fangping Yan; Chuntan Han; Xiqiang Wang; Changlian Tao; Jingfeng Liu (Science of The Total Environment, 2025)

Importance of viewing angle: Hotspot effect improves the ability of satellites to track terrestrial photosynthesis - Haoran Liu; Jingfeng Xiao; Dalei Hao; Fa Li; Fujiang Ji; Min Chen (Remote Sensing of Environment, 2025)

TG-Net: A Physically Interpretable Deep Learning Forecasting Model for Thunderstorm Gusts - Yunqing Liu; Lu Yang; Mingxuan Chen; Jianwei Si; Maoyu Wang; Wenyuan Li; Jingfeng Xu (Journal of Meteorological Research, 2025)

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

Experimental and numerical study on the flexural performance of composite beams with channel-section steel girder under fire exposure - Yong Liu; Qiuyu Xu; Lanhui Guo; Jingfeng Wang (Engineering Structures, 2025)

Phenacetin enhanced the inorganic nitrogen removal performance of anammox bacteria naturally in-situ enriched system - Yi Zhang; Jingfeng Gao; Jingqiang Zhao; Yifan Zhao; Ying Liu; Yi Guo; Tian Xie (Science of The Total Environment, 2024)

Insights into contrastive cellulose nanofibrils assembly and nanocrystals catalysis from dual regulations of plant cell walls - Yuanhang Ai; Hailang Wang; Peng Liu; Hua Yu; Mengdan Sun; Ran Zhang; Jingfeng Tang; Yanting Wang; Shengqiu Feng; Liangcai Peng (Science Bulletin, 2024)

Alterations in feeding preference and gastric emptying of giant freshwater prawn (Macrobrachium rosenbergii) following administration of varying quantities of fermented soybean meal - XingHui Cai; Jingyi Luo; Xiang Li; JingFeng Yang; XueMing Hua; Tao Liu (Aquaculture International, 2024)

A High-Precision, Ultra-Short Baseline Positioning Method for Full Sea Depth - Yeyao Liu; Jingfeng Xue; Wei Wang (Journal of Marine Science and Engineering, 2024)
To fulfill the demand for high-precision underwater acoustic positioning at full sea depth, an ultra-short baseline (USBL) positioning method with the square array based on the least squares estimating signal parameters via rotational invariance techniques (LS-ESPRIT) algorithm is presented in this paper. A combination of beam tracking and beamforming is employed to improve the accuracy of direction-of-arrival (DOA) estimation and, consequently, enhance overall positioning accuracy. In order to mitigate the issue of position jumping resulting from phase ambiguity in traditional four-element cross arrays, we have improved the stability of the positioning algorithm by utilizing a multi-element square array and employing the LS-ESPRIT algorithm for DOA estimation. Furthermore, the signal detection method integrating the correlation coefficient and ascending/descending chirp signals is employed to enhance the reliability of the location algorithm. Simulation analysis and experimental results demonstrate that the proposed algorithm effectively enhances positioning accuracy and improves the problem of jumping in positioning results.

A machine learning scheme for estimating fine-resolution grassland aboveground biomass over China with Sentinel-1/2 satellite images - Huaqiang Li; Fei Li; Jingfeng Xiao; Jiquan Chen; Kejian Lin; Gang Bao; Aijun Liu; Guo Wei (Remote Sensing of Environment, 2024)

Natural pyrite and ascorbic acid co-enhance periodate activation for inactivation of antibiotic resistant bacteria and inhibition of resistance genes transmission: A green disinfection process dominated by singlet oxygen - Hao Chen; Jingfeng Gao; Qian Wang; Ying Liu; Xiaoyu Fu; Yi Guo; Hanyi Wang; Yuxuan Wang; Jiawen An (Journal of Hazardous Materials, 2024)

Elimination of representative antibiotic-resistant bacteria, antibiotic resistance genes and ciprofloxacin from water via photoactivation of periodate using FeS2 - Fuyang Liu; Yutao Shen; Yanghui Hou; Jingfeng Wu; Yong Ting; Chenyi Nie; Meiping Tong (Journal of Hazardous Materials, 2024)

Characterization and projection of spatial and temporal changes in habitat quality of Sanjiangyuan based on land use change - Rui Jiang; Jingfeng Liu (Journal of Geographical Sciences, 2024)

Satellite-based monitoring of China's above-ground biomass carbon sink from 2015 to 2021 - Hongqian Fang; Lei Fan; Philippe Ciais; Jingfeng Xiao; Rasmus Fensholt; Jingming Chen; Frédéric Frappart; Weimin Ju; Shuli Niu; Xiangming Xiao; Wenping Yuan; Jiangzhou Xia; et al. (Agricultural and Forest Meteorology, 2024)

Sea cucumber intestinal osteotropic peptide promotes tibial fracture healing in osteoporotic mice by promoting glutamine metabolism - Haowen Yin; Sun Jin Hur; Tianqi Zhang; Hongying Liu; Hao Yue; Jingfeng Wang; Hongwei Zheng; Changhu Xue (Food Bioscience, 2024)

PGE2 Overexpressing Human Embryonic Stem Cell Derived Mesenchymal Stromal Cell Relieves Liver Fibrosis in an Immuno-suppressive Manner - Yan Zhong; Xiaohao Hu; Jingfeng Liu (Stem Cell Reviews and Reports, 2024)

Phenacetin promoted the rapid start-up and stable maintenance of partial nitrification: Responses of nitrifiers and antibiotic resistance genes - Yi Zhang; Zejie Wu; Yongqing Gao; Jingfeng Gao; Fangbo Bao; Yifan Zhao; Yi Guo; Ying Liu (Science of The Total Environment, 2024)

Removal of antibiotic resistant bacteria by the coupled system of ferrous ion activated peroxymonosulfate (PMS) and sodium percarbonate (SPC): Performance and mechanisms - Qian Wang; Jingfeng Gao; Hao Chen; Ying Liu; Xiaoyu Fu; Jiawen An; Hanyi Wang; Yuxuan Wang (Chemical Engineering Journal, 2024)

A Deep Learning Approach for Forecasting Thunderstorm Gusts in the Beijing-Tianjin-Hebei Region - Yunqing Liu; Lu Yang; Mingxuan Chen; Linye Song; Lei Han; Jingfeng Xu (Advances in Atmospheric Sciences, 2024)

Promoting the denitrification process by heavy metals in Liaohe Estuary sediment - Ming Hongxia; Zan Shuaijun; Liu Jiwen; Su Jie; Ren Kaijia; Lin Jiannan; Chen Quanrui; Shi Yinyin; Shi Tingting; Fan Jingfeng (Marine Pollution Bulletin, 2024)

CRISPR/Cas12b assisted loop-mediated isothermal amplification for easy, rapid and sensitive quantification of chronic HBV DNA in one-pot - Haipo Xu; Gengping Lin; Ronghua Chen; Zhixiong Cai; Yupeng Sun; Xiaolong Zhang; Bixing Zhao; Yongyi Zeng; Jingfeng Liu; Xiaolong Liu (Analytica Chimica Acta, 2024)

Mechanisms and clinical application of Xuebijing injection, a traditional Chinese herbal medicine–a systematic review - Mengchi Chen; Wenbo Shu; Jingfeng Zhang; Hongyuan Huang; Jianghua Liu (Advances in Traditional Medicine, 2024)

Mechanisms on the removal of gram-negative/positive antibiotic resistant bacteria and inhibition of horizontal gene transfer by ferrate coupled with peroxydisulfate or peroxymonosulfate - Xiaoyu Fu; Jingfeng Gao; Qian Wang; Hao Chen; Ying Liu; Liqin Zeng; Yukun Yuan; Hongxin Xu (Journal of Hazardous Materials, 2024)

The synergistic effect of periodate/ferrate (VI) system on disinfection of antibiotic resistant bacteria and removal of antibiotic resistant genes: The dominance of Fe (IV)/Fe (V) - Hao Chen; Jingfeng Gao; Qian Wang; Ying Liu; Lei Wu; Xiaoyu Fu; Yi Guo; Hanyi Wang; Yuxuan Wang (Journal of Hazardous Materials, 2024)

Efficient peroxymonosulfate activation by nanoscale zerovalent iron for removal of sulfadiazine and sulfadiazine resistance bacteria: Sulfidated modification or not - Ying Liu; Jingfeng Gao; Qian Wang; Hao Chen; Yi Zhang; Xiaoyu Fu (Journal of Hazardous Materials, 2024)

Corrigendum to “Energy availability and leaf area dominate control of ecosystem evapotranspiration in the southeastern U.S” [Agriculture and Forest Meteorology Volume 349 (2024)/109960] - Maricar Aguilos; Ge Sun; Ning Liu; Yulong Zhang; Gregory Starr; Andrew Christopher Oishi; Thomas L O'Halloran; Jeremy Forsythe; Jingfeng Wang; Modi Zhu; Devendra Amatya; Benju Baniya; et al. (Agricultural and Forest Meteorology, 2024)

High performance Pt/Nb2W3O14 catalyst for glycerol valorization to 1,3-propanediol - Jinghu Chen; Mingming Wang; Shude Zhang; Yaju Wang; Jingfeng Hua; Xiangtong Meng; Qineng Xia; Jieshan Qiu; Shaomin Liu (Chemical Engineering Journal, 2024)

Enhancing thermoelectric performance in GeTe through Ge enrichment regulation and AgCuTe alloying - Jingyi Lyu; Jingfeng Li; Wenwei Yang; Zhixing Chen; Zijie Ren; Zhanpeng Zhao; Shenghua Liu; Jing Shuai (Chemical Engineering Journal, 2024)

Erratum to: Bioinformatic analysis for potential biological processes and key targets of heart failure-related stroke - Chiyu Liu; Sixu Chen; Haifeng Zhang; Yangxin Chen; Qingyuan Gao; Zhiteng Chen; Zhaoyu Liu; Jingfeng Wang (Journal of Zhejiang University-SCIENCE B, 2024)

Energy availability and leaf area dominate control of ecosystem evapotranspiration in the southeastern U.S. - Maricar Aguilos; Ge Sun; Ning Liu; Yulong Zhang; Gregory Starr; Andrew Christopher Oishi; Thomas L O'Halloran; Jeremy Forsythe; Jingfeng Wang; Modi Zhu; Devendra Amatya; Benju Baniya; et al. (Agricultural and Forest Meteorology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Contrasting responses of relationship between solar-induced fluorescence and gross primary production to drought across aridity gradients - Ruonan Qiu; Ge Han; Xing Li; Jingfeng Xiao; Jiangong Liu; Songhan Wang; Siwei Li; Wei Gong (Remote Sensing of Environment, 2024)

Impact of the Three Gorges Dam on hydrological connectivity and vegetation growth of Poyang Lake floodplain, China - Jinfeng Zeng; Jingfeng Qiu; Zeyu Wu; Xinggen Liu; Yunliang Li (Journal of Hydrology, 2024)

Metabolic shifts in glycogen-accumulating organisms: Exploring carbon and phosphorus dynamics under two distinct phosphorus limitation modes - Shang Wang; Chenyu Li; Chunchun Zhang; Yuchao Liu; Sheng Li; Yiqiu Fang; Zhiqiang Shen; Jingfeng Wang (Journal of Cleaner Production, 2024)

Cleaning and upgrading of low-rank coal using a novel rotary triboelectric separator with the polyvinyl chloride as friction medium - Bin Yang; Lingtao Zhu; Jingfeng He; Bin Liu; Shibo Huang; Hao Chen; Wenjie Tang (Fuel, 2024)

MHY1485 promotes adriamycin sensitivity in HepG2 cells by inhibiting autophagy - Jingfeng Guo; Yingying Lei; Liwei Liu; Zhenzhen Wen; Bo Zhang; Jincun Fang; Guohui Liang; Qikun Guo; Jing Peng (Functional & Integrative Genomics, 2024)

Urban-rural gradient in vegetation phenology changes of over 1500 cities across China jointly regulated by urbanization and climate change - Yingying Ji; Wenfeng Zhan; Huilin Du; Shasha Wang; Long Li; Jingfeng Xiao; Zihan Liu; Fan Huang; Jiaxin Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Dynamics and biophysical controls of nocturnal water loss in a winter wheat-summer maize rotation cropland: a multi-temporal scale analysis - Xiaonan Guo; Jingfeng Xiao; Tianshan Zha; Guofei Shang; Peng Liu; Chuan Jin; Yucui Zhang (Agricultural and Forest Meteorology, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

Solar-induced chlorophyll fluorescence captures photosynthetic phenology better than traditional vegetation indices - Jingru Zhang; Alemu Gonsamo; Xiaojuan Tong; Jingfeng Xiao; Cheryl A. Rogers; Shuhong Qin; Peirong Liu; Peiyang Yu; Pu Ma (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Axial compressive performance of partially encased steel-concrete composite stub columns filled with lightweight aggregate concrete - Zhenghao Qian; Jingfeng Wang; Yong Liu; Qiuyu Xu (Engineering Structures, 2023)

Operation characteristics based on a novel performance model based on capacity utilization rate of a variable refrigerant flow air conditioning system - Hansong Xiao; Shurong Liu; Yunxiao Ding; Chunyuan Zheng; Bing Luo; Heng Niu; Jingfeng Shi; Baolong Wang; Qiang Song; Wenxing Shi (Energy and Buildings, 2023)

A comparative study of renewable and fossil fuels energy impacts on green development in Asian countries with divergent income inequality - Jiaqi Xu; Jingfeng Zhao; Wen Liu (Resources Policy, 2023)

Counting piglet suckling events using deep learning-based action density estimation - Haiming Gan; Jingfeng Guo; Kai Liu; Xinru Deng; Hui Zhou; Dehuan Luo; Shiyun Chen; Tomas Norton; Yueju Xue (Computers and Electronics in Agriculture, 2023)

The responses of microbial metabolic activity, bacterial community and resistance genes under the coexistence of nanoplastics and quaternary ammonium compounds in the sewage environment - Yi Zhang; Jingfeng Gao; Zhiqi Wang; Yifan Zhao; Ying Liu; Haoran Zhang; Mingyan Zhao (Science of The Total Environment, 2023)

Carbon exchange of forest plantations: global patterns and biophysical drivers - Xiaojuan Tong; Jingfeng Xiao; Peirong Liu; Jinsong Zhang; Jingru Zhang; Peiyang Yu; Ping Meng; Jun Li (Agricultural and Forest Meteorology, 2023)

BsEXLX of engineered Trichoderma reesei strain as dual-active expansin to boost cellulases secretion for synergistic enhancement of biomass enzymatic saccharification in corn and Miscanthus straws - Chengbao Xu; Tao Xia; Hao Peng; Peng Liu; Yihong Wang; Yanting Wang; Heng Kang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

An integrated approach to reconstructing snow cover under clouds and cloud shadows on Sentinel-2 Time-Series images in a mountainous area - Yanli Zhang; Yuyu Song; Changqing Ye; Jingfeng Liu (Journal of Hydrology, 2023)

Mitigating the inhibition of antibacterial agent chloroxylenol on nitrification system-The role of Rhodococcus ruber in a bioaugmentation system - Yi Guo; Jingfeng Gao; Yifan Zhao; Ying Liu; Mingyan Zhao; Ziqiao Li (Journal of Hazardous Materials, 2023)

Quaternary ammonium compounds promoted anoxic sludge granulation and altered propagation risk of intracellular and extracellular antibiotic resistance genes - Mingyan Zhao; Jingfeng Gao; Haoran Zhang; Yingchao Cui; Zhiqi Wang; Yifan Zhao; Yi Zhang; Ying Liu (Journal of Hazardous Materials, 2023)

Biological control efficacy of Bacillus licheniformis HG03 against soft rot disease of postharvest peach - Xiaoli Wang; Jingfeng Zhu; Huan Wei; Zhipeng Ding; Xiran Li; Zao Liu; Hongbao Wang; Yunpeng Wang (Food Control, 2023)

The spread of different resistance genes fractions in nitrification system under chronic exposure to varying alkyl chain length benzalkyl dimethylammonium compounds - Haoran Zhang; Jingfeng Gao; Mingyan Zhao; Zhiqi Wang; Dingchang Li; Zejie Wu; Yi Zhang; Ying Liu (Bioresource Technology, 2023)

Magnetically responsive nanoplatform targeting circRNA circ_0058051 inhibits hepatocellular carcinoma progression - Song You; Zijin Luo; Niangmei Cheng; Ming Wu; Yongping Lai; Fei Wang; Xiaoyuan Zheng; Yingchao Wang; Xiaolong Liu; Jingfeng Liu; Bixing Zhao (Drug Delivery and Translational Research, 2023)
Circular RNAs (circRNAs) are a class of highly stable and closed-loop noncoding RNA that are involved in the occurrence and development of hepatocellular carcinoma (HCC). However, little is known about the therapeutic role of circRNAs in HCC. We found that high circ_0058051 expression was negatively correlated with the prognosis of HCC patients. Circ_0058051 knockdown attenuated the proliferation and colony formation, meanwhile inhibited migration of HCC cells. Circ_0058051 may be used as a target for HCC gene therapy. We synthesized a novel small interfering RNA (siRNA) delivery system, PEG-PCL-PEI-C14-SPIONs (PPPCSs), based on superparamagnetic iron oxide nanoparticles (SPIONs). PPPCSs protected the siRNA of circ_0058051 from degradation in serum and effectively delivered siRNA into SMMC-7721 cells. Meanwhile, intravenous injection of the PPPCSs/siRNA complex could inhibit tumor growth in the subcutaneous tumor model. In addition, the nanocomposite is not toxic to the organs of nude mice. The above results show that PPPCSs/si-circ_0058051 complex may provide a novel and promising method of HCC treatment. Graphical abstract

Removal of antibiotic resistant bacteria, genes and inhibition of plasmid-mediated horizontal transfer by peroxymonosulfate: Efficiency and mechanisms - Ying Liu; Jingfeng Gao; Mingyan Zhao; Xiaoyu Fu; Yi Zhang; Haoran Zhang (Chemical Engineering Journal, 2023)

Hotspots of riverine greenhouse gas (CH4, CO2, N2O) emissions from Qinghai Lake Basin on the northeast Tibetan Plateau - Penglin Lin; Zhiheng Du; Lei Wang; Jingfeng Liu; Qian Xu; Jia Du; Rui Jiang (Science of The Total Environment, 2023)

Short-term stress of quaternary ammonium compounds on intracellular and extracellular resistance genes in denitrification systems - Mingyan Zhao; Jingfeng Gao; Ying Liu; Zhiqi Wang; Zejie Wu; Haoran Zhang; Yi Zhang (Chemical Engineering Journal, 2023)

Proteomic differences between Vibrio tubiashii strains with high- or low-virulence levels isolated from diseased ivory snail Babylonia areolata - Ruixuan Wang; Xiaojing Liu; Jiangyong Wang; Huizhu; Xiaozhi Lin; Jingfeng Sun; Hongli Mou; Ting Zhang; Xilan Ma (Aquaculture International, 2022)

Potato (Solanum tuberosum L.) non-specific lipid transfer protein StLTP6 promotes viral infection by inhibiting virus-induced RNA silencing - Kaijie Shang; Yang Xu; Weilin Cao; Xiaoying Xie; Yanru Zhang; Jingfeng Zhang; Hongmei Liu; Shumei Zhou; Xiaoping Zhu; Changxiang Zhu (Planta, 2022)

Expert consensus on organizing the multidisciplinary team (MDT) diagnosis and treatment of hepato-pancreato-biliary diseases in China - Binhao Zhang; Jian Zhou; Weifen Xie; Kaishan Tao; Shichun Lu; Xianglin Yuan; Lianxin Liu; Weilin Wang; Yilei Mao; Ping Bie; Jingfeng Liu; Xinyu Bi; et al. (Science China Life Sciences, 2022)

Decipher soil organic carbon dynamics and driving forces across China using machine learning - Huiwen Li; Yiping Wu; Shuguang Liu; Jingfeng Xiao; Wenzhi Zhao; Ji Chen; Georgii Alexandrov; Yue Cao (Global Change Biology, 2022)
The dynamics of soil organic carbon (SOC) play a critical role in modulating global warming. However, the long‐term spatiotemporal changes of SOC at large scale, and the impacts of driving forces remain unclear. In this study, we investigated the dynamics of SOC in different soil layers across China through the1980s to 2010s using a machine learning approach and quantified the impacts of the key factors based on factorial simulation experiments.Our results showed that the latest (2000–2014) SOC stock in the first meter soil (SOC 100 ) was 80.68 ± 3.49 Pg C, of which 42.6% was stored in the top 20 cm, sequestrating carbon with a rate of 30.80 ± 12.37 g C m −2 yr −1 since the 1980s. Our experiments focusing on the recent two periods (2000s and 2010s) revealed that climate change exerted the largest relative contributions to SOC dynamics in both layers and warming or drying can result in SOC loss. However, the influence of climate change weakened with soil depth, while the opposite for vegetation growth. Relationships between SOC and forest canopy height further confirmed this strengthened impact of vegetation with soil depth and highlighted the carbon sink function of deep soil in mature forest. Moreover, our estimates suggested that SOC dynamics in 71% of topsoil were controlled by climate change and its coupled influence with environmental variation (CE). Meanwhile, CE and the combined influence of climate change and vegetation growth dominated the SOC dynamics in 82.05% of the first meter soil. Additionally, the national cropland topsoil organic carbon increased with a rate of 23.6 ± 7.6 g C m −2 yr −1 since the 1980s, and the widely applied nitrogenous fertilizer was a key stimulus. Overall, our study extended the knowledge about the dynamics of SOC and deepened our understanding about the impacts of the primary factors.

PFC2D-based investigation on the mechanical behavior of anisotropic shale under Brazilian splitting containing two parallel cracks - Bo He; Jun Liu; Peng Zhao; Jingfeng Wang (Frontiers of Earth Science, 2021)

Study on the effects of the different polar group of EPA-enriched phospholipids on the proliferation and apoptosis in 95D cells - Yao Guo; Qin Zhao; Yingying Tian; Yuanyuan Liu; Ziyi Yan; Changhu Xue; Jingfeng Wang (Marine Life Science & Technology, 2021)
EPA-enriched phosphatidylcholine (EPA-PC) and EPA-enriched phosphatidylethanolamine (EPA-PE) are newly identified marine phospholipids. The polar group of phospholipids is known to influence EPA-phospholipid activity. However, the differences in anti-tumor effects between EPA-PC and EPA-PE have not been reported. In this study, we evaluated the effects of two forms of EPA on the proliferation and apoptosis in the lung-cancer cell line 95D as well as possible molecular mechanisms. Our results showed that EPA-PC effectively inhibited proliferative activity and promoted apoptosis of 95D cells in a dose-dependent manner, while EPA-PE had no effect on cell proliferation, although it slightly promoted apoptosis. Western blot results showed that EPA-PC and EPA-PE upregulated the expression of PPARγ, RXRα, and PTEN, and downregulated the PI3K/AKT signaling pathway. Furthermore, EPA-PC and EPA-PE induced the expression of the pro-apoptotic gene, Bax, and reduced the expression of the anti-apoptotic gene, Bcl-xl. Additionally, EPA-PC and EPA-PE promoted the release of cytochrome c and activated the apoptotic enzyme-cleaved caspase-3. These data suggest that the anti-tumor effect of EPA-phospholipids may be exerted via a PPARγ-related mechanism. EPA-PC was more efficacious as compared to EPA-PE, which might be due to the different polar groups of phospholipids.

Bioinformatic analysis for potential biological processes and key targets of heart failure-related stroke - Chiyu Liu; Sixu Chen; Haifeng Zhang; Yangxin Chen; Qingyuan Gao; Zhiteng Chen; Zhaoyu Liu; Jingfeng Wang (Journal of Zhejiang University-SCIENCE B, 2021)

Fucoidans from Thelenota ananas with 182.4 kDa Exhibited Optimal Anti-Adipogenic Activities by Modulating the Wnt/β-Catenin Pathway - Yuanyuan Liu; Na Wang; Yingying Tian; Yaoguang Chang; Jingfeng Wang (Journal of Ocean University of China, 2021)

Metabolic cold adaptation in the Asiatic toad: intraspecific comparison along an altitudinal gradient - Song Tan; Ping Li; Zhongyi Yao; Gaohui Liu; Bisong Yue; Jinzhong Fu; Jingfeng Chen (Journal of Comparative Physiology B, 2021)

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

Perfusion microvessel density in the cerebral cortex of septic rats is negatively correlated with endothelial microparticles in circulating plasma - Zhenzhou Wang; Jingfeng Liu; Xi Liu; Xinjie Guo; Tian Li; Ran Pang; Meili Duan (Metabolic Brain Disease, 2021)

Isolation and characterization of PoWRKY, an abiotic stress-related WRKY transcription factor from Polygonatum odoratum - Zhongping Wei; Jingfeng Ye; Zhiquan Zhou; Gang Chen; Fanjin Meng; Yifei Liu (Physiology and Molecular Biology of Plants, 2021)

Skin transcriptome, tissue distribution of mucin genes and discovery of simple sequence repeats in crucian carp ( Carassius auratus ) - Jie Bai; Xiucai Hu; Aijun Lü; Ruixia Wang; Rongrong Liu; Jingfeng Sun; Yuchen Niu (Journal of Fish Biology, 2020)
Crucian carp ( Carassius auratus ) is one of the major freshwater species and important food fish in China. Fish skin acts as the first line of defence against pathogens, yet its molecular and immune mechanism remains unclear. In this study, a de novo transcriptome assembly of C. auratus skin was performed with the Illumina Hiseq 2000 platform. A total of 49,154,776 clean reads were assembled, among which 60,824 (46.86%), 37,103 (28.59%), 43,269 (33.33%) unigenes were annotated against National Center for Biotechnology Information, Gene Onotology and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, respectively. KEGG Orthology categories were significantly involved in immune system (20.50%), signal transduction (18.04%) and mucosal mucin genes ( e.g. , muc2 , muc5AC , muc5B , muc17 , muc18 ). The high expression of muc18 gene was observed in brain; that of muc2 in intestine; and that of muc5AC in skin, liver, spleen, intestine and muscle. Moreover, the potential 28,928 simple sequence repeats with the three most abundant dinucleotide repeat motifs (AC/GT, AG/CT, AT/AT) were detected in C. auratus . To authors’ knowledge, this is the first report to describe the transcriptome analysis of C. auratus skin, and the outcome of this study contributed to the understanding of mucosal immune response of the skin and molecular markers in cyprinid species.

Malnutrition worsens fluorosis-induced damage in hypothalamic-pituitary-ovarian axis of rats - Yongmei Liu; Ling Li; Jingfeng Xu; Siwen Yu; Shijun Wang; Maojuan Yu; Wenbing Zou; Mingliang Cheng; Shuhua Xia (Molecular & Cellular Toxicology, 2019)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Contrasting ecosystem CO 2 fluxes of inland and coastal wetlands: a meta‐analysis of eddy covariance data - Weizhi Lu; Jingfeng Xiao; Fang Liu; Yue Zhang; Chang'an Liu; Guanghui Lin (Global Change Biology, 2017)
Wetlands play an important role in regulating the atmospheric carbon dioxide ( CO 2 ) concentrations and thus affecting the climate. However, there is still lack of quantitative evaluation of such a role across different wetland types, especially at the global scale. Here, we conducted a meta‐analysis to compare ecosystem CO 2 fluxes among various types of wetlands using a global database compiled from the literature. This database consists of 143 site‐years of eddy covariance data from 22 inland wetland and 21 coastal wetland sites across the globe. Coastal wetlands had higher annual gross primary productivity ( GPP ), ecosystem respiration ( R e ), and net ecosystem productivity ( NEP ) than inland wetlands. On a per unit area basis, coastal wetlands provided large CO 2 sinks, while inland wetlands provided small CO 2 sinks or were nearly CO 2 neutral. The annual CO 2 sink strength was 93.15 and 208.37 g C m −2 for inland and coastal wetlands, respectively. Annual CO 2 fluxes were mainly regulated by mean annual temperature ( MAT ) and mean annual precipitation ( MAP ). For coastal and inland wetlands combined, MAT and MAP explained 71%, 54%, and 57% of the variations in GPP , R e , and NEP , respectively. The CO 2 fluxes of wetlands were also related to leaf area index ( LAI ). The CO 2 fluxes also varied with water table depth ( WTD ), although the effects of WTD were not statistically significant. NEP was jointly determined by GPP and R e for both inland and coastal wetlands. However, the NEP / R e and NEP / GPP ratios exhibited little variability for inland wetlands and decreased for coastal wetlands with increasing latitude. The contrasting of CO 2 fluxes between inland and coastal wetlands globally can improve our understanding of the roles of wetlands in the global C cycle. Our results also have implications for informing wetland management and climate change policymaking, for example, the efforts being made by international organizations and enterprises to restore coastal wetlands for enhancing blue carbon sinks.

Enrichment, Distribution of Vanadium-Containing Protein in Vanadium-Enriched Sea Cucumber Apostichopus japonicus and the Ameliorative Effect on Insulin Resistance - Yanjun Liu; Qingxin Zhou; Yanlei Zhao; Yiming Wang; Yuming Wang; Jingfeng Wang; Jie Xu; Changhu Xue (Biological Trace Element Research, 2016)

Assessment of total and organic vanadium levels and their bioaccumulation in edible sea cucumbers: tissues distribution, inter-species-specific, locational differences and seasonal variations - Yanjun Liu; Qingxin Zhou; Jie Xu; Yong Xue; Xiaofang Liu; Jingfeng Wang; Changhu Xue (Environmental Geochemistry and Health, 2016)

Green Synthesis of Oxovanadium(IV)/chitosan Nanocomposites and Its Ameliorative Effect on Hyperglycemia, Insulin Resistance, and Oxidative Stress - Yanjun Liu; Xu Jie; Yongli Guo; Xin Zhang; Jingfeng Wang; Changhu Xue (Biological Trace Element Research, 2016)

Trends in the daily and extreme temperatures in the Qiantang River basin, China - Fang Xia; Xingmei Liu; Jianming Xu; Zhonggen Wang; Jingfeng Huang; Philip C. Brookes (International Journal of Climatology, 2015)
Temporal and spatial changes in the annual and seasonal temperatures in a typical basin of the Qiantang River were analysed based on the time series databases of daily temperatures from 14 meteorological stations. Both the Mann–Kendall ( MK ) trend test and simple linear regression analyses were employed to detect trends in the mean and extreme temperatures. The temperature changes during the three periods of 1960–1990, 1960–2000 and 1960–2006 were investigated at each meteorological station and over the entire basin as an average. The spatial and temporal changes were characterized by significant warming throughout the region, with the minimum temperature (Tn) increasing the most, particularly after 1990. Various percentiles of extreme temperatures, as well as their corresponding frequencies, were chosen to explore the trends of extreme climate change in this region. Linear regression analyses showed a significant warming trend in cold events both on an annual and seasonal basis, especially in the winter. Conversely, the hot events were dominated by an insignificant warming trend ( p > 0.05). When comparing the time series before and after 1990, trend shifts were apparent in both the mean and extreme temperatures, particularly in the spring and winter. In addition to the large‐scale circulation, regional factors may have influenced the observed climate change in the studied region. Climate change has already influenced human society by, for example, increasing the frequency of haze in the study region. We conclude that the warming here is mainly attributed to changes in the minimum temperature.

Differences in sex reversion and growth between normal and neomale stock in half-smooth tongue sole, Cynoglossus semilaevis - Qiaomu Hu; Song-Lin Chen; Fengtao Gao; Yangzhen Li; Shanshan Liu; Feng Liu; Jingfeng Yang; Min Du (Aquaculture International, 2014)

Estimating nitrogen concentration in rape from hyperspectral data at canopy level using support vector machines - Fumin Wang; Jingfeng Huang; Yuan Wang; Zhanyu Liu; Fayao Zhang (Precision Agriculture, 2013)

Functional study of immature dendritic cells co-transfected with IL-10 and TGF-beta 1 genes in vitro - Lihong Chen; Minglian Qiu; Wubing He; Aimin Huang; Jingfeng Liu (Molecular Biology Reports, 2012)

Trophic states of creeks and their relationship to changes in water level in Xixi National Wetland Park, China - Yufeng Li; Hongyu Liu; Jingfeng Hao; Nan Zheng; Xiao Cao (Environmental Monitoring and Assessment, 2012)

Genetic linkage maps of barfin flounder (Verasper moseri) and spotted halibut (Verasper variegatus) based on AFLP and microsatellite markers - Hongyu Ma; Songlin Chen; Jingfeng Yang; Siqing Chen; Hanwen Liu (Molecular Biology Reports, 2011)

Validation of artificial neural network techniques in the estimation of nitrogen concentration in rape using canopy hyperspectral reflectance data - Yuan Wang; Fumin Wang; Jingfeng Huang; Xiuzhen Wang; Zhanyu Liu (International Journal of Remote Sensing, 2009)